CLINICAL OUTCOME OF STROKE PATIENTS BASED ON THE NATIONAL INSTITUTES OF HEALTH STROKE SCALE (NIHSS) IN A TERTIARY HOSPITAL - Liunardo Bintang Pratama; Lisda Amalia; Cep Juli; Uni Gamayani; Asep Nugraha Hermawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Stroke is the second leading cause of death and the third cause of disability globally. Clinical outcomes caused by stroke are varied and influenced by various factors. Objective: This study aims to describe the clinical outcome of stroke patients based on neurological deficit using NIHSS at Dr. Hasan Sadikin General Hospital, Bandung. Methods: This study is a retrospective descriptive, cross-sectional study using secondary data from medical records recruited between January 2019 – December 2019 at the Department of Neurology Dr. Hasan Sadikin General Hospital Bandung with the total sampling method. Variables include demographic data, risk factors, and clinical characteristics. Neurological deficit was assessed using NIHSS. Data were analyzed and presented in the form of tables. Results: There were 202 subjects eligible for this study, including ischemic (71.8%) and intracerebral hemorrhage (28.2%) stroke patients. Most of the subjects were male (53%), aged ≥60 years (50,5%), presenting with onset >6 hours (72.3%), and had hypertension (92,1%). Most of the subjects have a moderate stroke (n=102;50.5%) based on the NIHSS score at admission and mild stroke (n=117;57.9%) based on the NIHSS score at discharge, with a motor deficit as the most common neurological deficit found. Conclusion: The majority of stroke patients presented with a moderate stroke on admission and had a clinical improvement during hospital treatment, with most of the patients experiencing a mild stroke on discharge based on NIHSS score. The motor deficit is the most common neurological deficit that affects clinical outcomes.